Evaluation of population monitoring strategies for greater sage-grouse (Centrocercus urophasianus) in northwestern Colorado - Shyvers, Jessica E., author; Noon, Barry R., advisor; Walker, Brett L., advisor; Aldridge, Cameron L., committee member; Crooks, Kevin R., committee member (Colorado State University. Libraries, 2017)
Population monitoring programs are essential for the proper management of wildlife species but, despite recent advances in methodologies, generating accurate and defensible estimates of population size and trend remains a key challenge for wildlife biologists and managers and effective monitoring programs generally require considerable resources, effort and funding. For this reason, managers often turn to the use of population indices to monitor species. The greater sage-grouse (Centrocercus urophasianus) is a species of conservation concern throughout its range in western North America. Since the 1950s, high counts of males at leks have been used as an index for monitoring populations and are often assumed to represent overall population trend. However, the relationship between the lek-count index and true population size is unclear, resulting from a reliance on numerous untested assumptions, and the reliability of these counts for monitoring population trend has been questioned. In addition, lek-count data do not provide information about the female population, a crucial component for assessing a population's growth potential. There is a need for development and evaluation of alternative methods to obtain reliable estimates of population trend and test assumptions underlying the lek-count index. We tested two novel methods for monitoring a small greater sage-grouse population in Northwest Colorado. We found that a large and variable proportion of the lekking male population was missing from lek-count data each year when not all leks were known and counted, the lek-count index poorly represented true annual male abundance in small populations, and the possibility of large annual variation in male-to-female sex ratio should be considered when extrapolating female abundance from male count data. Our results suggest that, while lek-count data may be useful for detecting large changes in the abundance of lekking males over time, observations of trend based on annual lek-count index data may misrepresent true population trend in relatively small populations.
Keywords: flock composition; greater sage-grouse; sex ratio; genetic mark-recapture; dual-frame surveys; lek-count index